Comparison between flunarizine and levetiracetam in paediatric migraine prophylaxis (Bangladesh Medical Journal Khulna, 2019)
Background: Migraine hampers child's life through school absence, limitation of home and social activities. The goal of prophylactic (preventive) therapy is to reduce headache frequency, headache days, and headache severity with minimum side effects.Objective: To evaluate the efficacy and tolerability of levetiracetam compared to flunarizine as prophylactic treatment of Migraine in children. Methods: This prospective study was carried out in the outpatient department of a tertiary care hospital in Bangladesh. A total of 105 children aged 6-15 years, diagnosed as migraine without aura, were enrolled. Patients were treated with flunarizine or levetiracetam for three months. Headache disabilities were evaluated at baseline and at the end of three months.Results: In flunarizine group, 54 children and in levetiracetam group, 51 children were enrolled. Among them thirty nine children in flunarizine group and 36 children in levetiracetam group completed the study. Headache frequency, headache days, VAS (Visual Analogue Scale) score and PedMIDAS (Paediatric Migraine Disability Assessment Score) score were evaluated at baseline and during the follow up. After three months, headache frequency, headache days, pain severity (Visual Analogue Scale score) reduced significantly compared to baseline (p